2020
DOI: 10.1042/bsr20194459
|View full text |Cite
|
Sign up to set email alerts
|

GPNMB contributes to a vicious circle for chronic obstructive pulmonary disease

Abstract: Osteoporosis (OP) is significant and debilitating comorbidity of chronic obstructive pulmonary disease (COPD). We hypothesize that genetic variance identified with OP may also play roles in COPD. We have conducted a large-scale relation data analysis to explore the genes implicated with either OP or COPD, or both. Each gene linked to OP but not to COPD was further explored in a mega-analysis and partial mega-analysis of 15 independently collected COPD RNA expression datasets, followed by gene set enrichment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Additionally, MMP9 is a crucial regulator implicated in ESCC outcome and prognosis [41], and its expression can be regulated by GLI2 in melanoma cells [42]. A previous document proved that GPNMB can influence MMP9 expression in chronic obstructive pulmonary disease [43]. Our data also showed that Tan can downregulate MMP9 expression by diminishing GPNMB level in ESCC cells.…”
Section: Plos Onesupporting
confidence: 66%
“…Additionally, MMP9 is a crucial regulator implicated in ESCC outcome and prognosis [41], and its expression can be regulated by GLI2 in melanoma cells [42]. A previous document proved that GPNMB can influence MMP9 expression in chronic obstructive pulmonary disease [43]. Our data also showed that Tan can downregulate MMP9 expression by diminishing GPNMB level in ESCC cells.…”
Section: Plos Onesupporting
confidence: 66%
“…MMP-12 belongs to the matrix metalloproteinases family, which contributes to the remodeling of the small airways and to the proteolytic degradation of the alveolar wall matrix, leading to emphysema [21]. GPNMB, an endogenous glycoprotein, can influence the pathogenesis of COPD, for instance, through its contribution to tissue remodeling in COPD by promoting the secretion of MMP-9, another matrix metalloproteinase [22]. CTSK is a cysteine protease that is stimulated by inflammatory cytokines and released after tissue injury, contributing to the destruction of connective tissues in the lungs [23].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MMP9 is a crucial regulator implicated in ESCC outcome and prognosis [ 41 ], and its expression can be regulated by GLI2 in melanoma cells [ 42 ]. A previous document proved that GPNMB can influence MMP9 expression in chronic obstructive pulmonary disease [ 43 ]. Our data also showed that Tan can down-regulate MMP9 expression by diminishing GPNMB level in ESCC cells.…”
Section: Discussionmentioning
confidence: 99%